Romanian vector in theforeign policy of the Republic of Moldova: The political dimension of thefoundations and dynamics of bilateral relations between Chisinau and Bucharest - Golovchenko, Dmitry P. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения)
The article examines the foundations of bilateral relations between Moldova and Romania since the collapse of the USSR. The author analyzes the phenomenon of Moldovan unionism and its influence on the foreign policy of Chisinau in the Romanian direction. Individual stages of Moldovan-Romanian relations are highlighted in the context of regular transformations of the internal political situation in Moldova.